Management of Bone Defects and Complications After Bone Tumor Resection Using Ilizarov Method - Kai Zheng; Xiu‐Chun Yu; Jinfang Cai; Ming Xu; Haocheng Cui; Qian Chen; Jing‐Yu Zhang (Orthopaedic Surgery)
ABSTRACT Objective Ilizarov technology is highly effective in addressing complex orthopedic challenges. This study aims to describe our experience with distraction osteogenesis in managing bone tumors in the lower extremity, focusing on composite bone defects and associated complications. Methods A retrospective clinical study was conducted to analyze patients with primary bone tumors who underwent distraction osteogenesis using the Ilizarov method from 2010 to 2020. Some young children received epiphyseal distraction and bone transport as part of their sarcoma surgical treatment. Additionally, external fixation, bone transport, or limb lengthening were employed to address complex postoperative complications associated with bone tumors. The clinical outcomes assessed included the patient's general information, the location of bone defects, the length of bone repair, the status of bone healing, and limb function. Results Eleven patients were followed up for an average of 66 months (range, 24–132 months). The average length of repaired bone defects was 13 cm (range, 2.5–32 cm). The cohort comprised three females and eight males, with ages at presentation ranging from 6 to 42 years (mean, 18 years). The sites of involvement included the distal femur (n = 4), femoral diaphysis (n = 3), proximal tibia (n = 2), and the distal tibia (n = 2). Nine patients were diagnosed with osteosarcoma, while one presented with Ewing's sarcoma and another with a giant cell tumor of bone. Three young children were successfully treated with epiphyseal stretching; however, one patient experienced treatment failure. Additionally, seven patients underwent external fixation to address complex postoperative complications, including infection, bone defects, and limb shortening. At the last follow‐up, with the exception of one failure, the average Musculoskeletal Tumor Society (MSTS) limb function scores for the remaining 10 patients were 25 (range, 21–30). Three months post‐fixator removal, the Asociación Latinoamericana de Oncología (ASAMI) bone score was rated as excellent in 63.6% (7/11) of patients, whereas the ASAMI function score was excellent in 36.4% (4/11) and good in 54.5% (6/11) of cases. Conclusion The Ilizarov method demonstrates some clinical value in the resection and reconstruction of bone tumors, as well as in the management of postoperative complications associated with such tumors.